Pandangan Dalam Ajaran Agama Islam Terhadap Program Keluarga Berencana - Miranda Alfisah Suwardi; Liza Amilea Rahman; Sagati Fourrizqiyah (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
This article discusses the family planning program in Indonesia from an Islamic perspective. Indonesia, as a country with the largest Muslim population, faces challenges in managing population growth. Family planning, which began in 1968, aims to improve family welfare by regulating the number and spacing of children. Although there is controversy among the public regarding the acceptance of this program, many scholars consider it a positive step if done with good intentions. The research method used is journal review and descriptive, focusing on the views of scholars and related literature. This article explains the definition of family planning, its objectives, the types of contraceptives used, as well as the views of Islamic law regarding its implementation. Some scholars state that the use of temporary contraception is permissible, as long as it does not absolutely deny the gift of offspring. In contrast, permanent methods such as vasectomy and tubectomy are prohibited unless there are medical reasons. In conclusion, Islam provides room for the practice of family planning under certain conditions, promoting family welfare and reproductive health without violating the principles of sharia.